DYNAMIC COLLISION DETECTION OF UNMANNED SHIP BASED ON WIRELESS COMMUNICATION - Luo, Jie; Li, Jie; Dong, Wenhai (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
In order to improve the detection accuracy of the collision detection system for unmanned ships at sea, this paper proposes a dynamic collision detection method based on improved ZigBee network wireless communication technology. The collision parameter detection model of unmanned ships at sea based on the ZigBee network and wireless communication network control is constructed. The communication network model is established by using wireless sensor network communication and radio frequency identification tag recognition technology. The experimental results show that the system can more accurately analyze and detect the collision of unmanned ships at sea and judge the route information of ships when there are obstacles. The collision dynamic detection accuracy of the system is 25% higher than that of traditional methods on average, and the performance is superior.